1998
DOI: 10.1021/la980515s
|View full text |Cite
|
Sign up to set email alerts
|

Base-Pair Formation of Self-Organizing RNA Amphiphiles within Two Dimensions

Abstract: In an attempt to get a better insight in specific base pairing by self-organization of DNA or RNA, the synthesis of a complete set of monoalkyl ribonucleotides is described. The thermodynamic phase and mixing properties of these self-organizing RNA amphiphiles were analyzed within two dimensions using film balance technique. The pure compounds form stable monolayers at the air−water interface on a physiological buffer. In analogy to base-paired RNA or DNA in solution, the monolayers were mostly stabilized by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…[11] Another related class of amphiphiles is based on low-molecular-weight hydrophobic groups attached to ODNs or individual nucleotides. The latter are known as nucleolipids and have been extensively studied for their interactions with membranes, potential biomedical applications, [12] and their supramolecular organization, both into monolayers [13] and micelles. [14] The ability of these aggregates to carry information is limited by the presence of only individual nucleotides, but pyrimidine bases modified at the 5-position with a range of hydrophobic moieties have also been integrated into DNA sequences by using solid-phase synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Another related class of amphiphiles is based on low-molecular-weight hydrophobic groups attached to ODNs or individual nucleotides. The latter are known as nucleolipids and have been extensively studied for their interactions with membranes, potential biomedical applications, [12] and their supramolecular organization, both into monolayers [13] and micelles. [14] The ability of these aggregates to carry information is limited by the presence of only individual nucleotides, but pyrimidine bases modified at the 5-position with a range of hydrophobic moieties have also been integrated into DNA sequences by using solid-phase synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] A variety of synthetic strategies have been used to prepare nucleotide-based amphiphiles, [14][15][16] including coupling reactions of a monoalkylphosphate with a nucleoside 17 and enzymatic catalysis. [18][19][20][21] A significant amount of the literature devoted to this family of amphiphiles describes mainly longchain alkyl ester nucleoside-5 0 -monophosphate derivatives (Scheme 1, i.e. C 16 UMP).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Moreover, much emphasis is placed upon the interaction between the host monolayers and guest components in the subphase, and no attention is attracted to the competition of the host-host interactions with the host-guest ones. Our recent studies indicated that the monolayer of cytosine-functionalized nucleolipids on the aqueous guanosine subphase underwent an orientation change not only in base moiety but also in alkyl chain in comparison to the monolayer on pure water, 19,20 and these revealed the interconversion of hydrogen bonds between adjacent cytosine moieties and between cytosine and guanosine base pairs in the courses of molecular recognition and the phase transition behaviors of the corresponding LB films.…”
Section: Introductionmentioning
confidence: 99%